Catholicisme et nationalisme dans l’Italie fasciste : la réponse clérico-fasciste à la sécularisation d’une nation catholique (1919-1929) - Matteo BARAGLI (Amnis)
This article analyses the issue of clerico-fascism, or national-catholicism, within the framework of Italian political life of the Twenties. After the rise to power of fascism, the clerico-fascists supported the new regime, which they supposed would promote catholic renewal in opposition to the secularisation of Italian society and of its liberal institutions. The common background on which national-catholics and fascists could reach an agreement was that of nationalism and the support of a pro-catholic policy. The Vatican attitude towards the clerico-fascism was complex. The Vatican hierarchies appreciated the pro-catholic policy of the fascist regime, but at the same time distrusted the political autonomy that Fascism and clerico-fascists claimed from the Holy See. The ratification of the Lateran Pacts sanctioned in the end the final acknowledgement of Italy as a « catholic nation ». This result emphasized the effectiveness – pointed to by the Vatican as a model for other catholic countries – of national-catholicism as a successful alternative to liberal and democratic secularism.